An opportunity for global antimicrobial stewardship research: Refugee populations - Payal K. Patel; Preeti Mehrotra; Joseph B. Ladines-Lim (Cambridge University Press, 2022)
Antimicrobial resistance is a well-known global health threat that has higher prevalence in the refugee population. Although guidance has been provided by the World Health Organization and Centers for Disease Control and Prevention on implementing antimicrobial stewardship in lower- and middle-income countries, as well as by the United Nations Refugee Agency on other infection prevention and control efforts, no specific guidance exists for implementation of stewardship in this population. We highlight challenges specific to this population, review recent studies of interest within this space, and propose a research agenda to help move stewardship forward in the refugee population. We advocate for the importance of this issue, particularly given recent current events of geopolitical volatility that render this population more vulnerable, in the setting of its already well-known numerous health challenges.